The Philosophy of Knowledge in Islam and Its Role in Shaping Educational Management Strategies - Mulyani, Nina; Ansori, Ahmad Faisol; Pahrudin, Agus; Sudjarwo, Sudjarwo; Rahman, Bujang (Universitas Islam Negeri Raden Intan Lampung, 2025)
The enduring relevance of Islamic epistemology lies in its ability to harmonize spiritual and intellectual pursuits, providing a comprehensive foundation for addressing the ethical and operational challenges of modern educational systems. Despite its rich heritage, the application of Islamic philosophy of knowledge in shaping educational management strategies remains underexplored. This study investigates how Islamic epistemology, grounded in divine revelation (wahyu) and human reasoning (‘aql), can serve as a transformative framework for aligning ethical values with practical governance needs. By focusing on principles such as amanah (trust), shura (consultation), and adl (justice), the research demonstrates how these concepts can inform leadership, policy-making, and institutional governance in educational systems. Adopting a qualitative literature review approach, this study analyzes primary texts like the Qur'an and Hadith, alongside contemporary academic contributions, to contextualize Islamic philosophical principles within modern educational paradigms. The findings reveal the potential of integrating Islamic knowledge into educational governance structures, fostering environments that balance intellectual growth, moral integrity, and social responsibility. While limited to literature-based analysis, this research bridges the gap between theoretical discourse and practical application, offering a robust framework for future empirical validation and contextual adaptation. The proposed framework includes three core Islamic principles amanah (trust), shura (consultation), and adl (justice) which are operationalized across educational leadership, policy formulation, and institutional governance structures.